1985
DOI: 10.3109/00016358509046507
|View full text |Cite
|
Sign up to set email alerts
|

The effect of removable partial dentures on mastication and dietary intake

Abstract: Masticatory efficiency, the subjective experience of masticatory performance, and dietary intake were evaluated in 19 subjects who were treated with a removable partial denture in the lower jaw. The subjects were tested on three occasions: before treatment, with the dentures when free from symptoms, and about 4 months after the dentures were inserted. Masticatory efficiency and the subjective experience of masticatory performance increased significantly after the subjects were provided with the dentures, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 22 publications
1
48
0
4
Order By: Relevance
“…Several studies showed similar results even though the methods used were different. 2,3,5,26 The change in dietary habits resulting from a declining masticatory performance over a period of years must not be underestimated. This change is unlikely to be reversed even though the masticatory efficiency is improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed similar results even though the methods used were different. 2,3,5,26 The change in dietary habits resulting from a declining masticatory performance over a period of years must not be underestimated. This change is unlikely to be reversed even though the masticatory efficiency is improved.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Although masticatory performance tends to decline with decreasing number of teeth, the relationship between masticatory function and impaired food intake has been established more rarely for partially edentulous than for fully edentulous patients. 6,7 Several studies report that an impaired ability to chew has a negative effect on food selection and diet [8][9][10] which is not necessarily reflected by the haematological analysis of nutrition markers.…”
Section: Introductionmentioning
confidence: 98%
“…15,28,29 Although some studies have been reported on the effects of replacement of posterior teeth with conventional removable partial dentures on masticatory performance, the results are controversial. [30][31][32] In addition, subjective chewing ability was not impaired when subjects have more than 20 well-distributed teeth. 15,33,34 Therefore, prosthetic intervention in the presented situation may be unnecessary if patients do not perceive any impairment of chewing ability.…”
Section: -11mentioning
confidence: 92%
“…27,28 Yapılan çalışmalar, hastaların posterior diş kaybını, daha fazla çiğneyerek, 29 daha büyük besin parçaları yutarak ya da daha yumuşak besinleri seçe-rek karşılayabileceğini göstermiştir. 30 Bazı araştırmalar distal uzantılı hareketli parsiyel protezin çiğneme verimliliğini artırdığını göstermesine rağmen 29,31 , Gunne'nin 30 bir araştırmasına göre diyet alışkanlığında büyük değişiklikler beklenmemelidir. Kısaltılmış dental arkların çiğneme kapasitesi, çiğ havuç gibi kolay absorbe edilebilen besinler çiğneme testlerinde temel alınarak belirlenmiştir.…”
Section: Sda Ve çIğneme Fonksiyonuunclassified